Comparison of DNA Sequencing and a Line Probe Assay for Detection of Human Immunodeficiency Virus Type 1 Drug Resistance Mutations in Patients Failing Highly Active Antiretroviral Therapy - Servais, Jean (American Society for Microbiology, 2001)
The resistance of human immunodeficiency virus type 1 (HIV-1) to drugs is a major cause of antiretroviral treatment failure. We have compared direct sequencing to a line probe assay (LiPA) for the detection of drug resistance-related mutations in 197 clinical samples, and we have investigated the sequential appearance of mutations under drug pressure. For 26 patients with virological failure despite the use of two nucleoside analogues and one protease inhibitor (indinavir [n = 6], ritonavir [n = 10], and saquinavir [n = 10]), genotypic resistance assays were carried out retrospectively every 3 months for up to 2 years by using direct sequencing (TruGene; Visible Genetics) and a LiPA for detection of mutations in the reverse transcriptase (INNO-LiPA HIV-1 RT; Innogenetics) and the protease (INNO-LiPA HIV Protease, prototype version; Innogenetics) genes. Comparison of the results from both assays found rare major discrepancies (<1% of codons analyzed). INNO-LiPA detected more wild-type–mutant mixtures than sequencing but suffered from a high rate of codon hybridization failures for the reverse transcriptase. LiPA detected earlier and more frequently than sequencing the transient mixed virus population that contained I84V, which appears before V82A in the protease sequence. Mutations M461, G48V, and L90M were often transient and drug pressure related. In conclusion, direct sequencing and LiPAs give concordant results for most clinical isolates. LiPAs are more sensitive for the detection of mixed virus populations. Mutation I84V appears in minor populations in the early steps of the pathways of resistance to indinavir and ritonavir. The fact that some mutations can be found only transiently and in minor virus populations highlights the importance of a low detection limit for resistance assays.